The Incredible Hulk [videorecording (Blu-Ray)] - Norton, Edward; Tyler, Liv; Roth, Tim; Hurt, William; Nelson, Tim Blake; Burrell, Ty, 1967-; Ferrigno, Lou (Universal Studios Home Entertainment, 2008)
Scientist Bruce Banner has been living in the shadows, scouring the earth for an antidote. Warmongers dream of abusing his powers and won't leave Bruce alone. He suffers from his constant need to be with the only woman he has ever love, Betty Ross, and Bruce knows that he must return to civilization. The brilliant doctor is ruthlessly pursued by a nightmarish beast of pure adrenaline and aggression called The Abomination whose powers match that of the Hulk. Now, a fight of epic proportions ensues as Bruce must call upon the hero within to rescue New York City from total destruction.